Initial Reports of the Deep Sea Drilling Project 1970
DOI: 10.2973/dsdp.proc.4.106.1970
|View full text |Cite
|
Sign up to set email alerts
|

Site 27

Abstract: The northern margin of the Demerara Abyssal Plain is bordered by a low ESE-WNW trending rise known as the Barracuda Ridge. North of South America, the eastern margin of the Demerara Abyssal Plain is formed by the Barbados Ridge. An extensive sedimentary section of the Barbados Ridge is exposed on the island of Barbados and consists of a series of radiolarian to planktonic foraminiferal and calcareous nannofossil biogenic sediments interlayered with ash beds. This series, known as the Oceanic Formation, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The thickness of the recent Quaternary sediments filling the Barracuda trough is very high (locally higher than 2 sTWT, corresponding probably to more than 2 km; Patriat et al, 2011; Pichot et al, 2012; Fig. 11), which is consistent with the data collected at DSDP drilling site 27 (Bader et al, 1970) and…”
Section: Long Distance Channel Pattern In the Abyssal Plainsupporting
confidence: 81%
“…The thickness of the recent Quaternary sediments filling the Barracuda trough is very high (locally higher than 2 sTWT, corresponding probably to more than 2 km; Patriat et al, 2011; Pichot et al, 2012; Fig. 11), which is consistent with the data collected at DSDP drilling site 27 (Bader et al, 1970) and…”
Section: Long Distance Channel Pattern In the Abyssal Plainsupporting
confidence: 81%
“…2). According to the stratigraphic record reported at Site 27 (Bader et al, 1970) and other regional studies (Wright et al, 1984;Dolman, 2000), the quaternary succession generally comprises interbedded distal turbidites within hemipelagic sediments. The Quaternary sequence onlaps against a progressive unconformity (horizon H02) ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The ANTIPLAC cruise was designed to cross these DSDP-ODP drilling sites. Because of the highest amount of quaternary sediments recovered at Site 27 (Bader et al, 1970) this site is of particular importance to study recent sedimentation processes occurring seaward of the Barbados accretionary prism. Considering velocity laws from previous studies in the area (Bangs et al, 1990;Dolman, 2000), borehole depth and stratigraphic boundaries reported at Site 27 were converted into time (Patriat et al, 2011;Pichot et al, 2012;).…”
Section: Seismic Calibration Based On Borehole Datamentioning
confidence: 99%